Chia (Salvia hispanica L.) Seed Soaking, Germination, and Fatty Acid Behavior at Different Temperatures - Daniel Cabrera-Santos; Cesar A. Ordoñez-Salanueva; Salvador Sampayo-Maldonado; Jorge E. Campos; Alma Orozco-Segovia; Cesar M. Flores-Ortiz (Agriculture, 2021)
The temperature reduces the viability and seed vigor; however, the effect of temperature on imbibition and fatty acid profile has not been studied. Chia (Salvia hispanica L.) seeds have a substantial quantity of oil, making them a potential study model for fatty acid metabolism. Therefore, we explore the effect of temperature (10, 20, and 30 °C) on chia seed imbibition, germination, and fatty acid profile by GC-MS. Imbibition FI occurs within the first hour in all the treatments; while FII and FIIend elapse with an hour of difference at 20 °C and 30 °C. The highest viability and germination rate were observed at 30 °C; while the highest concentrations of all fatty acids, except oleic acid, were observed at 20 °C. Maximum fatty acid concentrations were detected at FI and FIIend; while at 30 °C, different patterns for saturated and unsaturated fatty acids and three linolenic acid isomers were observed. A shorter FII is associated with earlier germination; the increase in concentration in fatty acids after 3 h and a negative correlation between linoleic and linolenic acid observed at 20 °C were related to a higher germination efficiency. At 30 °C, isomer formation is related to homeoviscous cell membrane adaptation.